The Effect of Service Quality and Customer Satisfaction on Customer Loyalty at Bidakara Savoi Homan Hotel - Setiadi, Yadi (Universitas Pendidikan Indonesia (UPI), 2023)
The hotel business, which deals with accommodation, is the same as other industries. It has been growing and there are more and more hotel buildings in every place, both in big cities and small towns. Hospitality companies are competing with each other for market share, which demands better service quality. If the hospitality industry is able to create customer satisfaction, it will create a good relationship between the company and its customers. This provides a good basis for repeat purchases and the creation of customer loyalty. Customer loyalty or consumer loyalty is a measure of consumer loyalty to the use of a brand. Companies need to prioritize strategies by trying to create customer loyalty.This study aims to determine the effect of service quality and customer delight on customer loyalty at Bidakara Savoy Homan Hotel Bandung. The research method used is a descriptive method with a quantitative approach. While this research was conducted by distributing questionnaires to 100 respondents. The sampling chosen is purposive random sampling, the data collected is then managed and analyzed using statistical tests. And the results of the analysis of service quality and customer delight, the t-count value is 2.149 and the t-table is 1.98, it can be concluded that Ho is rejected and H2 is accepted and the sig value is 2.149 1.98 with a significance result of 0.035 0.050, which means that there is a significant influence between customer delight on customer loyalty, the F-count value is 12. 967 and F-table 3.09, this means that the F-count value is greater than the F-table value (12.967 3.09), with significant results (0.037 0.050), so it can be concluded that accepting H3 rejects Ho, which means that Service Quality and Customer Delight together have an effect on Customer Loyalty.